The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3389/fphy.2019.00165
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Ring Disclinations Driven by Active Nematic Shells

Abstract: When dispersed in thermotropic nematic liquid crystal oils, surfactant-ladden aqueous droplets often lead to the formation of a equatorial ring disclination in the nearby nematic matrix as a result of a balance between elasticity and interfacial energy. In this experimental work, the aqueous phase contains an extract of cytoskeletal proteins that self-assemble into an active quasi-two-dimensional shell featuring self-sustained periodic flows. The ensuing hydrodynamic coupling drives the surrounding liquid crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…From the precedent considerations, it is clear that active nematic emulsions, the active counterparts of the nematic emul- Referring to the LC encapsulation of the microtubule/kinesin active material, the obvious question to be addressed is the eventual coupling between the active defects driving cortical flows inside the droplets and the passive singularities sitting around them in the surrounding passive LC. We analyzed this question in a couple of recent contributions published by Guillamat et al [24], and Hardoüin et al [25]. We briefly review on what follows the most paradigmatic scenario as reported in [24].…”
Section: Active Nematic Emulsionsmentioning
confidence: 97%
See 1 more Smart Citation
“…From the precedent considerations, it is clear that active nematic emulsions, the active counterparts of the nematic emul- Referring to the LC encapsulation of the microtubule/kinesin active material, the obvious question to be addressed is the eventual coupling between the active defects driving cortical flows inside the droplets and the passive singularities sitting around them in the surrounding passive LC. We analyzed this question in a couple of recent contributions published by Guillamat et al [24], and Hardoüin et al [25]. We briefly review on what follows the most paradigmatic scenario as reported in [24].…”
Section: Active Nematic Emulsionsmentioning
confidence: 97%
“…The mentioned variety of observed behaviors is likely to be due to both a quite wide range of droplet size distribution, added to the difficulty to guarantee a uniform partition of the components of the active sample and of the chemical surfactant. More details can be found in the paper published by Hardoüin et al [25].…”
Section: Active Nematic Emulsionsmentioning
confidence: 99%
“…5a and b). [63][64][65][66][67][68][69][70][71] During one semi-period, the defects move from a tetrahedral configuration to a planar one or vice versa. For larger |a| values, such an oscillatory motion is inherited by the shell itself, which, again by virtue of the mechanical coupling between defects and curvature, periodically deforms from spherical to elliptical (Fig.…”
Section: Protrusion Formation In Nematic Shellsmentioning
confidence: 99%
“…For instance, they facilitate self-assembly and the formation of metamaterials [28,29], and enable novel control of topological defects [27,30,31]. While there have been studies of active nematic droplets in a host passive liquid crystal [32,33], colloidal inclusions in host active nematics have not been looked at previously.…”
Section: Introductionmentioning
confidence: 99%